2021
DOI: 10.3389/fspor.2021.619291
|View full text |Cite
|
Sign up to set email alerts
|

Warm-Ups and Coaches' Perceptions: Searching for Clues to Improve Injury Prevention in Youth Basketball

Abstract: Introduction: Regular use of neuromuscular training (NMT) warm-up programs improves performance and prevents injuries. However, low level of adoption of these programs remains a problem. Understanding the current warm-ups in youth basketball and coaches' perceptions on injury prevention can guide the design of superior implementation strategies. This study describes warm-ups in youth basketball and coaches' injury prevention-related knowledge, attitudes, beliefs, and information sources.Methods: Youth basketba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 53 publications
3
20
0
Order By: Relevance
“…Our findings that context mediates enactment of behavior mechanisms seems to be consistent with recent studies (Räisänen et al 2021;Owoeye et al, 2020) and the findings related to realist evaluation (Mitchell, 1997;Pawson & Tilley, 1994), and policy enactment studies in physical education and sport pedagogy (Hammond et al, 2020;Landi et al, 2021;O'Gorman et al, 2021). Owoeye et al (2020) found coaches were inclined to remove strength and balance related tasks in favor of exercises deemed to be more relevant to basketball performance.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings that context mediates enactment of behavior mechanisms seems to be consistent with recent studies (Räisänen et al 2021;Owoeye et al, 2020) and the findings related to realist evaluation (Mitchell, 1997;Pawson & Tilley, 1994), and policy enactment studies in physical education and sport pedagogy (Hammond et al, 2020;Landi et al, 2021;O'Gorman et al, 2021). Owoeye et al (2020) found coaches were inclined to remove strength and balance related tasks in favor of exercises deemed to be more relevant to basketball performance.…”
Section: Discussionsupporting
confidence: 90%
“…to vary (Norcross et al, 2016;Owoeye et al, 2020;Räisänen et al, 2021). A recent study by Owoeye et al (2020), found that coaches altered NMT programs based on perceived relevance to performance as well as player interest.…”
mentioning
confidence: 99%
“…Of the coaches that reported using a warm-up routine in the past 12 months, the use of NMT components (i.e., aerobic, balance, strength, agility) within their warm-ups was variable with most coaches always using aerobic components and few using balance. This is similar to findings in Canadian youth basketball, where coaches reported including an aerobic component in their warm-up, but only 27% utilized balance exercises prior to attending a workshop on a NMT warm-up (Raisanen et al, 2021 ). Within the literature, balance appears to be the most neglected component of coaches' previous warm-ups, though research suggests that it is an effective and important component (Brunner et al, 2019 ).…”
Section: Discussionsupporting
confidence: 83%
“…Ninety percent of those who verify the information use basic Google search [ 33 ]. In the injury prevention context, 32% of basketball coaches are sourcing their injury prevention knowledge from the Internet; the only more popular resources are other coaches [ 11 ]. Without the high-quality resources freely available online, it may be difficult to achieve the goal of reducing injuries in sport.…”
Section: Discussionmentioning
confidence: 99%
“…The Internet’s ubiquity and low entry barrier allows for easy dissemination of health-related information online [ 10 ]. Online injury prevention resources may contribute to a wider distribution of injury risk reduction programmes and their subsequent implementation [ 11 ]. On the Internet, there are no restrictions on the format, the number of words, figures or diagrams used, and videos are relatively easy to implement.…”
Section: Introductionmentioning
confidence: 99%